1991
DOI: 10.1152/jappl.1991.71.4.1277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on human adductor pollicis muscle function

Abstract: The effect of aging on the voluntary and electrically evoked contractile properties of the human adductor pollicis muscle was investigated in 70 healthy male subjects aged 20-91 yr, 10 subjects for each decade. Maximum isometric voluntary force declined significantly (range of P values less than 0.001-0.05) after the age of 59 yr, dropping by the eighth decade to 57.6% of the level recorded in the second decade. A significant shift (P range less than 0.001-0.05) to the left of the frequency-force curve after u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
125
2
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 0 publications
13
125
2
7
Order By: Relevance
“…Since the fusion of muscle contraction should occur more readily at low rates of excitation in type I fibers, the decrease in the motor unit firing rate in the elderly would be a neurophysiological adaptation to activate type I muscle fibers efficiently and minimize high-frequency fatigue (Moritani et al 1985). In fact, Narici et al (1991) had already showed that aged muscle was tetanized at lower fusion frequencies in the human adductor pollicis muscle by nerve stimulation (Narici et al 1991). Also, a negative relationship between the maximal motor unit firing rate and afterhyperpolarization (AHP) in the tibialis anterior muscle was demonstrated in the elderly (r = −0.37, p = 0.004) but not in the young (r = −0.05, p = 0.72) (Christie and Kamen 2010), suggesting that AHP elongation contributes to the age-related decrease in the motor unit firing rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since the fusion of muscle contraction should occur more readily at low rates of excitation in type I fibers, the decrease in the motor unit firing rate in the elderly would be a neurophysiological adaptation to activate type I muscle fibers efficiently and minimize high-frequency fatigue (Moritani et al 1985). In fact, Narici et al (1991) had already showed that aged muscle was tetanized at lower fusion frequencies in the human adductor pollicis muscle by nerve stimulation (Narici et al 1991). Also, a negative relationship between the maximal motor unit firing rate and afterhyperpolarization (AHP) in the tibialis anterior muscle was demonstrated in the elderly (r = −0.37, p = 0.004) but not in the young (r = −0.05, p = 0.72) (Christie and Kamen 2010), suggesting that AHP elongation contributes to the age-related decrease in the motor unit firing rate.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven adult subjects Յ50 yr old (19-50 yr) constituted the adult group (four female and seven male). This age range was selected to exclude subjects likely to have significant functional changes as found in hand muscles of subjects older than 60 yr (40). Eight elderly subjects from 67 to 85 yr old were studied (three female and five male).…”
Section: Methodsmentioning
confidence: 99%
“…In normal weight individuals, ageing is known to be accompanied by a significant decline in maximal strength and explosive force production, 21,22 as well as power output, 23,24 which seem to be explained to a great extent by the reduction in muscle mass, 25,26 although age-related changes in hormone balance 27 and a lower capacity of elderly for neuromuscular response in controlling postural sway 28 can play an important role. In agreement with the age-related decrease in muscle performance presently observed in our obese population, the decline in maximal strength and power has been reported to take place at a rate of about 1-3% per year in lower limb extensor muscles.…”
Section: Muscular Power Output In Obesitymentioning
confidence: 99%